2014
DOI: 10.1186/1476-4598-13-166
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-200c inhibits invasion and metastasis of human non-small cell lung cancer by directly targeting ubiquitin specific peptidase 25

Abstract: BackgroundGrowing evidence indicates that miR-200c is involved in carcinogenesis and tumor progression in non-small-cell lung cancer (NSCLC). However, its precise biological role remains largely elusive.MethodsThe functions of miR-200c and USP25 in migration/invasion and lung metastasis formation were determined by transwell and tail vein injection assays, respectively. The potential regulatory targets of miR-200c were determined by prediction tools, correlation with target protein expression, and luciferase r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
83
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 45 publications
(48 reference statements)
1
83
0
Order By: Relevance
“…Liu et al (13) identified that miR-200c inhibited invasion, migration and proliferation of bladder cancer cells. Li et al (25) showed that miR-200c inhibited metastasis and invasion of human non-small cell lung cancer cells (25). Therefore, the present study expanded the current understanding of miR-200c functioning in human cancer.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Liu et al (13) identified that miR-200c inhibited invasion, migration and proliferation of bladder cancer cells. Li et al (25) showed that miR-200c inhibited metastasis and invasion of human non-small cell lung cancer cells (25). Therefore, the present study expanded the current understanding of miR-200c functioning in human cancer.…”
Section: Discussionmentioning
confidence: 60%
“…MicroRNAs (miRs) are a type of small non-coding RNA (19)(20)(21)(22)(23)(24)(25) nucleotides) that possess prominent roles in the regulation of genes (6). MiRs typically inhibit gene expression by directly binding the 3'-untranslated region of their target messenger (m)RNAs, causing repression of translation or mRNA degradation (7).…”
Section: Introductionmentioning
confidence: 99%
“…First, the levels of USP25 mRNAs are significantly increased in breast cancer tissues and non-small cell lung cancer (NSCLC) tissues as compared with adjacent tissues (Deng et al 2007;Li et al 2014), although the mechanisms that lead to this up-regulation remain to be elucidated. Second, USP25 can promote cell growth and tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…It is released from degraded proteins by disassembly of the polyubiquitin chains, which is mediated by ubiquitin-specific proteases, members of the ubiquitin-specific processing family of proteases for deubiquitination of proteins [7][8][9]. E3 ubiquitin ligases and deubiquitylases play an important role in cancer [7,10,11].…”
mentioning
confidence: 99%